2014
DOI: 10.1101/002063
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Holsteins Favor Heifers, Not Bulls: Biased Milk Production Programmed during Pregnancy as a Function of Fetal Sex

Abstract: Mammalian females pay high energetic costs for reproduction, the greatest of which is imposed by lactation. The synthesis of milk requires, in part, the mobilization of bodily reserves to nourish developing young. Numerous hypotheses have been advanced to predict how mothers will differentially invest in sons and daughters, however few studies have addressed sexbiased milk synthesis. Here we leverage the dairy cow model to investigate such phenomena. Using 2.39 million lactation records from 1.49 million dairy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 96 publications
4
39
0
Order By: Relevance
“…However, our results provide further evidence that the “biological recipe” of milk has the potential to differ for sons and daughters, as shown in previously for macro‐constituents and calcium concentration in rhesus monkey milk [Hinde, ; Hinde et al, ]. If the developmental trajectory or priorities differ for sons and daughters, either in the interest of their own or their mother's reproductive success, we can predict that natural selection will shape milk composition and/or infant receptor expression and nutrient assimilation to be sex‐differentiated [Hinde, ; Hinde et al, , ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, our results provide further evidence that the “biological recipe” of milk has the potential to differ for sons and daughters, as shown in previously for macro‐constituents and calcium concentration in rhesus monkey milk [Hinde, ; Hinde et al, ]. If the developmental trajectory or priorities differ for sons and daughters, either in the interest of their own or their mother's reproductive success, we can predict that natural selection will shape milk composition and/or infant receptor expression and nutrient assimilation to be sex‐differentiated [Hinde, ; Hinde et al, , ].…”
Section: Discussionsupporting
confidence: 79%
“…Nutritional status of mothers during pregnancy and lactation affects both the composition of breast milk as well as the overall volume of milk produced per day [Robyn et al, ], although these effects are not necessarily mediated by differences in maternal body mass index [Gambian women, Prentice and Prentice, ]. The “biological recipe” of milk synthesized for sons can differ from milk synthesized for daughters [macaques, Hinde, ; humans, Fujita et al, ; Powe et al, ; Thakkar et al, but not always—see Quinn ] and likely reflects, in part, divergent developmental priorities and trajectories [Hinde et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…It is not known how or whether this physiological process is a result of programming, but it appears to be established before the second lactation. Animal studies suggest that some aspects of maternal milk production and offspring feeding behavior and growth are actually programmed during pregnancy (Cowley et al, ; Hinde, Carpenter, Clay, & Bradford, ). This occurs through genetic imprinting; Grb 10 appears to influence both maternal milk production and milk consumption by the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…For example, milk production and quality in rhesus macaques vary with maternal parity and offspring sex (Hinde, ), and mothers rearing daughters produced milk with higher calcium content (Hinde et al, ). Additionally, even when milk synthesis does not seem to differ between sons and daughters, the magnitude and windows of sensitivity to milk constituents can differ between sons and daughters (Hinde, Carpenter, Clay, & Bradford, ). Sex differences may therefore extend to milk hormones and their effects on the pace of early postnatal growth.…”
Section: Introductionmentioning
confidence: 99%
“…Sex differences may therefore extend to milk hormones and their effects on the pace of early postnatal growth. Indeed, the effects of milk GCs on other offspring outcomes such as temperament (Grey, Davis, Sandman, & Glynn, ; Hinde et al, ; Sullivan et al, ) and social and cognitive functioning (Dettmer et al, ) have been found to vary as a function of infant sex.…”
Section: Introductionmentioning
confidence: 99%